Therapeutic alliance in two treatments for adolescent anorexia nervosa1. Issue 1 (27th July 2012) - Forsberg, Sarah; LoTempio, Elizabeth; Bryson, Susan; Fitzpatrick, Kathleen Kara; Le Grange, Daniel; Lock, James
Abstract Objective: The aim of this study was to examine the relationship between therapeutic alliance and treatment outcome (remission status) in family‐based treatment (FBT) and adolescent‐focused therapy (AFT) for adolescents with anorexia nervosa (AN). Method: Independent observers rated audiotapes of early therapy sessions using the Working Alliance Inventory‐Observer Version (WAI‐o). Outcome was defined using established cut‐points for full and partial remission. To control for effects of early symptom improvement, changes in weight‐ and eating‐related psychopathology prior to the alliance session were calculated and entered as a covariate in each analysis. Results: Participants in AFT had significantly higher alliance scores; however, overall scores were high in both therapies. The alliance was not a predictor of full remission for either treatment, though it was a non‐specific predictor for partial remission. Discussion: Therapeutic alliance is achievable in adolescents with AN in both AFT and FBT, but demonstrated no relationship to full remission of the disorder. © 2012 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)